Antara Digital atau Cetak: Menakar Kemampuan Literasi Sains Peserta Didik melalui penerapan Modul Pembelajaran Fisika Berbasis Science, Environment, Technology, and Society (SETS) - Ikbal, Muh Syihab; A. Jusriana; Nur Inayah Umrah; Andi Uswatun Hasanah (Al-Khazini, 2025)
This study aims to examine the differences in students’ scientific literacy skills through the implementation of SETS-based digital modules and SETS-based printed modules among Grade X MIPA students at SMA Negeri 8 Gowa. The research employed a quasi-experimental method with a matching-only post-test control group design. The study population consisted of 248 Grade X MIPA students, from which a sample of 66 students was selected using the two-step matching sampling technique. The sample was divided into two groups: an experimental group and a control group. The instrument used to measure scientific literacy was a multiple-choice test. Data analysis comprised both descriptive and inferential statistical techniques. The results indicated that students in both the experimental and control groups demonstrated scientific literacy at the proficient level, with mean scores of 54.67 and 51.27, respectively. Based on the inferential analysis, the Asymp. Sig. (2-tailed) value was found to be greater than 0.05, suggesting that there is no statistically significant difference in scientific literacy skills between students taught using the digital module and those taught using the printed module, both developed based on the SETS (Science, Environment, Technology, and Society) approach.